Frontolimbic neural circuit changes in emotional processing and inhibitory control associated with clinical improvement following transference‐focused psychotherapy in borderline personality disorder. Issue 1 (8th October 2015) - Perez, David L.; Vago, David R.; Pan, Hong; Root, James; Tuescher, Oliver; Fuchs, Benjamin H.; Leung, Lorene; Epstein, Jane; Cain, Nicole M.; Clarkin, John F.; Lenzenweger, Mark F.; Kernberg, Otto F.; et al.
Abstract : Aims: Borderline personality disorder (BPD) is characterized by self‐regulation deficits, including impulsivity and affective lability. Transference‐focused psychotherapy (TFP) is an evidence‐based treatment proven to reduce symptoms across multiple cognitive–emotional domains in BPD. This pilot study aimed to investigate neural activation associated with, and predictive of, clinical improvement in emotional and behavioral regulation in BPD following TFP. Methods: BPD subjects ( n = 10) were scanned pre‐ and post‐TFP treatment using a within‐subjects design. A disorder‐specific emotional–linguistic go/no‐go functional magnetic resonance imaging paradigm was used to probe the interaction between negative emotional processing and inhibitory control. Results: Analyses demonstrated significant treatment‐related effects with relative increased dorsal prefrontal (dorsal anterior cingulate, dorsolateral prefrontal, and frontopolar cortices) activation, and relative decreased ventrolateral prefrontal cortex and hippocampal activation following treatment. Clinical improvement in constraint correlated positively with relative increased left dorsal anterior cingulate cortex activation. Clinical improvement in affective lability correlated positively with left posterior‐medial orbitofrontal cortex/ventral striatum activation, and negatively with right amygdala/parahippocampal activation. Post‐treatment improvements in constraint were predicted by pre‐treatment right dorsal anterior cingulate cortex hypoactivation, and pre‐treatment left posterior‐medial orbitofrontal cortex/ventral striatum hypoactivation predicted improvements in affective lability. Conclusions: These preliminary findings demonstrate potential TFP‐associated alterations in frontolimbic circuitry and begin to identify neural mechanisms associated with a psychodynamically oriented psychotherapy.